Penerapan model pembelajaran mind mapping untuk meningkatkan pemahaman konsep kegiatan ekonomi dengan memanfaatkan sumber daya alam kelas iv sekolah dasar - Putri, Brigitta Averiano Resha; Sukarno, Sukarno; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2019)
Aim of this research is improving concept comprehension of economic activity by utilizing natural resources. Subjects of this research are 31 from IV class at Purwoprajan II Elementary School. This research is classroom action research, with 2 cycles implementation of actions. Each cycle consist of planning, action, observation, and reflection.Technique of data collection comprise of observation, interview, test, and document. To validity data of this research, using technique triangulation and source triangulation. The technique for analyze data is descriptive comparative and critical analyze. Research procedure held using cycle model comprise planning, action, observation, and reflection. This research found that mind mapping learning model improving concept comprehension of economic activity by utilizing natural resources of 4th grade at Purwoprajan II Elementary School. It can be seen from the rise of class average. Before application of mind mapping, the class average is 56,93. In first cycle, class average is 66,95. And in second cycle the average is 82,14. This research can improve completeness percentage, before application of mind mapping the percentage is 20,7%, at first cycle 41,94%, and second cycle is 83,87%.